Inhibition of the JAK2/STAT3 pathway and cell cycle re‐entry contribute to the protective effect of remote ischemic pre‐conditioning of rat hindlimbs on cerebral ischemia/reperfusion injury. (23rd November 2022) - Zhao, Yongmei; Ding, Mao; Yan, Feng; Yin, Jie; Shi, Wenjuan; Yang, Nan; Zhao, Haiping; Fang, Yalan; Huang, Yuyou; Zheng, Yangmin; Yang, Xueqi; Li, Wei; et al.
Abstract: Aims: Remote ischemic pre‐conditioning (RIPC) protects against ischemia/reperfusion (I/R) injury. However, the mechanisms underlying this protection remain unclear. In the present study, we investigated the role of Janus‐activated kinase 2 (JAK2)/signal transducer and activator of transcription 3 (STAT3) pathway and cell cycle arrest, and their relationship with neuronal apoptosis following RIPC. Methods: A rat cerebral I/R injury model was induced by middle cerebral artery occlusion (MCAO), and AG490 was used to investigate the mechanisms of RIPC. p‐JAK2‐, p‐STAT3‐, cyclin D1‐, and cyclin‐dependent kinase 6 (CDK6) expression was assessed by Western blotting and immunofluorescence staining. Results: RIPC reduced the infarct volume, improved neurological function, and increased neuronal survival. Furthermore, p‐JAK2 and p‐STAT3 were detected during the initial phase of reperfusion; the expression levels were significantly increased at 3 and 24 h after reperfusion and were suppressed by RIPC. Additionally, the MCAO‐induced upregulation of the cell cycle regulators cyclin D1 and CDK6 was ameliorated by RIPC. Meanwhile, cyclin D1 and CDK6 were colocalized with p‐STAT3 in the ischemic brain. Conclusion: RIPC ameliorates the induction of the JAK2/STAT3 pathway and cell cycle regulators cyclin D1 and CDK6 by MCAO, and this net inhibition of cell cycle re‐entry by RIPC is associated with downregulation of STAT3 phosphorylation. Abstract : Three days' RIPC mitigates I/R injury by decreasing the induction of JAK2/STAT3 pathway and cell cycle regulators cyclin D1 and CDK6 by MCAO, and this net inhibition of cell cycle re‐entry by RIPC is associated with downregulation of STAT3 phosphorylation.